ArtiInstilling Critical Thinking for Empowering Students Contribution Toward SDGs Realization - Ferdi Nazirun Sijabat; Muhammad Ridha Ramli; Suri Amilia; Rahmad Tantawi (Bansigom Na Publisher, 2025)
Critical thinking is a fundamental skill necessary for addressing global challenges, including the Sustainable Development Goals (SDGs). This paper explores strategies to instill critical thinking among students, empowering them to actively contribute to SDGs realization. By integrating critical thinking into education, students develop problem-solving abilities, ethical reasoning, and innovative mindsets. This study employs a qualitative approach, analyzing teaching methodologies and their impact on students' engagement with SDGs-related projects. The findings indicate that critical thinking fosters greater awareness and proactive behaviors, enabling students to tackle SDGs challenges effectively. The paper concludes with recommendations for integrating critical thinking into curricula to sustain long-term contributions to SDGs